Effect of katuk (Sauropus androgynus) powder supplementation on the levels of progesterone (P4) and estradiol-17β (E2) hormones in kacang goat (Capra aegragus) - HERI DWI PUTRANTO; GADING PUTRA HASIBUAN; YOSSIE YUMIATI; SURA MENDA GINTING (Smujo International, 2017)
Putranto HD, Hasibuan GP, Yumiati Y, Ginting SM. 2017. Effect of katuk (Sauropus androgynus) powder supplementation on the levels of progesterone (P4) and estradiol-17β (E2) hormones in kacang goat (Capra aegragus). Nusantara Bioscience 9: 86-91. Kacang goat (Capra aegragus) is one of Indonesian endemic ruminant species which commonly retained by the community in Indonesia. This species is classified as a small ruminant which has many benefits i.e easy to be domesticated and to adapt, and has an economical value especially for saving purposes to farmers in marginal areas. This study aimed to observe the effects of the katuk powder supplementation (Sauropus androgynus) in the feed of kacang goats on the level of reproductive hormones (progesterone (P4) and estradiol-17β (E2)) in female kacang goats. A total of 9 female kacang goats which meet the prerequisite samples i.e reaching the age of a sexual maturity, having a homogenous weight (12.00 ± 1.00 kg) and in healthy condition were then devided into three groups of treatments using a Completely Randomized Design method. Each treatments consisted of 3 kacang goats as a replication. The treatments consisted of: (i) feed without katuk powder supplementation (control),(ii) feed with the concentration of katuk powder supplementation was 3% of kacang goat’s body weight, and (iii) feed with the concentration of katuk powder supplementation was 6% of kacang goat’s body weight. After 60 days of treatments, the results showed that the supplementation of katuk powder on female kacang goats had no significant effect on the level of progesterone and estradiol-17β in the first sampling (day-0, P>0.05), however the treatment had a significant effect to the level of progesterone and estradiol-17β on the second sampling (day-28) and the third sampling (day-56) with a significance level of P<0.05. It was concluded that the supplementation of katuk powder could increase the level of progesteron and estradiol-17β hormones in kacang goats. The katuk powder supplementation about 3% of goat weight has sufficiently increased the level of reproduction hormones in female kacang goats.